Pathological manifestations on the facades of historic buildings: a case study of the Igreja de Nossa Senhora do Carmo in São Luís – MA (Research, Society and Development, 2022)
The historical monuments are important works for the society, because they keep part of the history of places and people from several centuries, so it is important that they are properly preserved, so that this history is not lost. Thus, this work aims to identify and analyze the pathological manifestations found in historic buildings, through the case study of the facade of the Church of Our Lady of Carmel and propose possible causes and restoration therapies. Despite being several centuries old, it was noted that the church's facade remains well preserved in relation to other buildings in the region, however, it was possible to find some malfunctions. It was possible to detect them through site visits and visual and photographic inspections, as well as comparisons with the bibliographies studied. With this, it was possible to identify and examine the pathological manifestations found, and to suggest some restorations, so that the facade of the church of Nossa Senhora do Carmo continues with a good level of preservation.